Efforts to optimize spinal health in adolescents: Enhancing awareness of scoliosis and body posture at SMA Negeri 3 South Tangerang City - Ichlasul Adzani; Ananda Putri Rifanty; Sofia Aufa Oktafiani; Rafienna Fernanda Isnindriani; Hana Kaamilah; Rifannia Zulfa Deandatita; Mochamad Syaidil Firdaus; Desmawati Desmawati; Haryanti Jaya Harjani (Community Empowerment, 2024)
The issue of spinal problems, especially scoliosis, is common, with 80-85% of cases occurring during adolescence, predominantly affecting females. Scoliosis in adolescents is a significant concern due to its potential impact on growth and development, particularly during rapid growth phases. The program aims to enhance students' knowledge and awareness of spinal health and posture to prevent scoliosis and other spinal issues. The implementation method includes lectures on “scoliosis & body posture.” A total of 39 participants took part in the activity, and based on pre-test and post-test averages, there was an improvement in understanding and awareness among participants after receiving information on “scoliosis & body posture.”